Pemanfaatan Gadget Pada Mahasiswa Universitas Muhammadiyah Surakarta - Putri, Khusnul Arizqa Winda Kusuma; , Dr. Sri Lestari, M.Si (2016)
The aims of study is to describe the use of gadget as communication media among student. Researcher used the phenomenological qualitative approach that collected by open ended questionnaire and semi-structure interview. Questionnaire has been given to second semester students of Muhammadiyah University of Surakarta were 180 respondents consisted of 92 males and 88 females. Interview took samples of four informan consisted of 2 males and 2 females. The data were analyzed thematically. The study found that the gadget is use by student to communicate and looking for sensation, looking for information, entertainment, doing assignment, and use as life style. Gadget using is different between male and female on gadget activity and while gathering. Social interaction by social media was formed interaction pattern are assosiative and disosiative. Meanwhile social interaction on student has changed in family and society.